Incidence of spiraling whiteflies Aleurodicus dspersus Russell (Hemiptera: Aleyrodidae) and its natural enemies on guava orchards (Journal of Bio-Science, 2018)
Population dynamics of spiraling whitefly and its natural enemies on guava orchards are essential for improvement of existing pest control methods. To find out the seasonal abundance of guava whitefly and its natural enemies and levels of infestations were studied on guava orchards severely infested by A. dispersus. Five guava plants were selected randomly. To determine each stage of the insect density, six leaves comprising upper, middle and lower part of each plant were randomly sampled. Sooty mould infested leaves and presence of natural enemies of A. dispersus were also recorded. The highest number of egg mass (5.0) and nymphs (10.0) per leave were found in the month of September. The highest (0.20%) ladybird beetle, Scymnus sp. (Coccinellidae: Coleoptera) and Encarsia sp. (0.15%) were found in the months of October and January, respectively. The number of leaves infested with sooty mould fungus was estimated highest (93%) during October to January. A. dispersus population was peak in the months of August to January and the associated natural enemies may successfully contribute to the existing pest control methods.J. bio-sci. 24: 67-74, 2016